3, 7-Dideazaneplanocin: Synthesis and antiviral analysis. Issue 3 (December 2017) - Yin, Xue-Qiang; Schneller, Stewart W
Objective: To synthesize 3, 7-dideazaneplanocin and evaluate its antiviral potential. Methods: The target 3, 7-dideazaneplanocin has been prepared in five steps from a readily available cyclopentenol. A thorough in vitro antiviral analysis was conducted versus both DNA and RNA viruses. Results: A rational synthesis of 3, 7-dideazaneplanocin was conceived and successfully pursued in such a way that it can be adapted to various analogs of 3, 7-dideazaneplanocin. Using standard antiviral assays, no activity for 3, 7-dideazaneplanocn was found. Conclusion: Two structural features are necessary for adenine-based carbocyclic nucleosides (like neplanocin) for potential antiviral properties: (i) inhibition of S-adenosylhomocysteine hydrolase and/or (ii) C-5′ activation via the mono-nucleotide. These two requisite adenine structural features to fit these criteria are not present in in the target 3, 7-dideazaneplanocin: (i) an N-7 is necessary for inhibition of the hydrolase and the N-3 is claimed to be essential for phosphorylation at C-5′. Thus, it is not surprising that 3, 7-dideazaneplaoncin lacked antiviral properties.